2022
DOI: 10.1002/slct.202201803
|View full text |Cite
|
Sign up to set email alerts
|

A Facile and Inexpensive Way to Synthesize N‐trifluoromethyl Compounds

Abstract: A facile way to introduce CF3 groups on a large variety of secondary amines has been developed, avoiding expensive and hazardous reagents. The advantage of the method could be demonstrated by obtaining crystalline tert‐butyl 4‐(trifluoromethyl)piperazine‐1‐carboxylate, a compound that previously only had been obtained as an oil. A major problem is the extreme sensitivity of these compounds towards moisture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…It has been previously reported that alkyl N −CF 3 amines, particularly those without electron‐withdrawing groups attached, are susceptible to fluorine elimination;[ 2 , 5 ] furthermore, the groups of Schindler, Yi, and Xiao each reported independently that degradation can occur rapidly upon flash column chromatography purification. [ 5a , 10a , 10d ] To confirm that the aqueous conditions of the LCMS were the cause of the observed transformation, compound 2 f was subjected to the relevant aqueous ammonium bicarbonate conditions used in the LCMS analysis, which resulted in the formation of carbamoyl fluoride 6 a in 27 % isolated yield (Scheme 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously reported that alkyl N −CF 3 amines, particularly those without electron‐withdrawing groups attached, are susceptible to fluorine elimination;[ 2 , 5 ] furthermore, the groups of Schindler, Yi, and Xiao each reported independently that degradation can occur rapidly upon flash column chromatography purification. [ 5a , 10a , 10d ] To confirm that the aqueous conditions of the LCMS were the cause of the observed transformation, compound 2 f was subjected to the relevant aqueous ammonium bicarbonate conditions used in the LCMS analysis, which resulted in the formation of carbamoyl fluoride 6 a in 27 % isolated yield (Scheme 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the pioneering work by Schoenebeck et. al ., [9] this approach has been used to synthesise a wide range of N −CF 3 amines in good yields under mild reaction conditions [5a,9,10] . Despite the Schoenebeck method employing the bench‐stable (Me 4 N)SCF 3 in a one‐pot protocol, the drawback of this method is the use, and associated relative expense, of super‐stoichiometric quantities of AgF [11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction conditions were applicable to a wide range of disubstituted nitrogen, with substituents including phenyl, heteroaromatic or alkyl. Recently, Schindler et al applied chlorodithiophenylformiate as an electrophile and successfully obtained phenyl aminodithioate 30 [ 60 ]. Then trifluoromethylamines 31 were generated after the desulfurization and fluorination.…”
Section: Five-membered Heterocyclesmentioning
confidence: 99%